2015
DOI: 10.1371/journal.pone.0139785
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Immunization with DOTAP Cationic Liposomes Combined with DC-Cholesterol Induces Potent Antigen-Specific Mucosal and Systemic Immune Responses in Mice

Abstract: Despite the progress made by modern medicine, infectious diseases remain one of the most important threats to human health. Vaccination against pathogens is one of the primary methods used to prevent and treat infectious diseases that cause illness and death. Vaccines administered by the mucosal route are potentially a promising strategy to combat infectious diseases since mucosal surfaces are a major route of entry for most pathogens. However, this route of vaccination is not widely used in the clinic due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 55 publications
4
47
0
2
Order By: Relevance
“…Cationic liposomes deserve attention and further development since the ability of nanoparticles to penetrate the nasal mucus is obviously dependent not only on the size, but also, primarily, on the surface charge of particles [24]. In addition, the positive charge of liposomes plays an important role in the in vitro processes of interaction with cells epithelium [25] and as a mucosal adjuvant [8,26]. We applied the cationic liposome intranasal drug delivery approach in the treatment of organophosphorus poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…Cationic liposomes deserve attention and further development since the ability of nanoparticles to penetrate the nasal mucus is obviously dependent not only on the size, but also, primarily, on the surface charge of particles [24]. In addition, the positive charge of liposomes plays an important role in the in vitro processes of interaction with cells epithelium [25] and as a mucosal adjuvant [8,26]. We applied the cationic liposome intranasal drug delivery approach in the treatment of organophosphorus poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing this mode of carrier mechanism, various studies have used administration of intranasal liposomes in many diseases, such as Alzheimer (Corace et al, 2014; Zheng et al, 2015), Parkinson (Migliore et al, 2014) and tuberculosis (Leemans et al, 2001). Also, intranasal liposomes have also been used in the preparation of vaccines against bacterial and fungal infectious diseases such as pneumonia, influenza, and tuberculosis (Khatri et al, 2008; Romero and Morilla, 2011; Tada et al, 2015; Tiwari et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Liposomes were prepared as described earlier [19]. Briefly, 10 μmol of total lipids (DOTAP:DC-chol at 1:1 mol ratios) were evaporated to dryness in a glass tube and desiccated for at least 1 h in vacuo.…”
Section: Preparation Of Cationic Liposomesmentioning
confidence: 99%
“…The detailed molecular mechanism(s) behind the adjuvant effects of the cationic liposomes are not completely elucidated. We have previously reported that cationic liposome promotes antigen uptake into the DCs located at nasal-associated lymphoid tissues (NALTs) in vivo [19] [20]. Although, how the cationic liposome increases antigen uptake by DCs remains unclear till date.…”
mentioning
confidence: 99%